(untitled) (International Seven Journal of Health Research, 2024)
Introduction: Anesthesia management in elderly patients presents distinct challenges due to physiological changes related to aging. Comorbidities, physical frailty and increased risk of postoperative complications are important aspects to be considered. Methods: Systematic reviews of the literature and analyzes of clinical and experimental studies that addressed the management of anesthesia in elderly patients were carried out. Articles published in English, Spanish and Portuguese were selected. The keywords used were "anesthesia in the elderly", "preoperative assessment", "anesthetic techniques", "intraoperative monitoring", "postoperative pain control" and "prevention of complications". Results: Comprehensive and individualized preoperative assessment was identified as crucial for identifying and treating comorbidities and physical frailty in elderly patients. The choice of the appropriate anesthetic technique depends on the type of surgery and the patient’s clinical conditions. Careful monitoring during anesthesia, including blood pressure, heart rate, oxygenation and capnography, is essential to detect and intervene early on hemodynamic and respiratory changes. Postoperative pain control in the elderly requires an individualized approach, with appropriate use of analgesics and regional blocks. Complication prevention strategies, such as optimizing hydration, glycemic control, early mobilization and appropriate use of medications, are essential to reduce the risk of delirium, infection and cognitive dysfunction. Conclusion: Anesthesia management in elderly patients requires an individualized and comprehensive approach, taking into account physiological changes related to aging and associated comorbidities. Careful preoperative assessment, appropriate choice of anesthetic technique, strict intraoperative monitoring, postoperative pain control and prevention of complications are essential to ensure a safe perioperative period and successful recovery in the elderly. Keywords: anesthesia in the elderly, preoperative assessment, anesthetic techniques, intraoperative monitoring, postoperative pain control, prevention of complications.